GAMBARAN KEMAMPUAN KREATIVITAS SISWA SLOW LEARNER (LAMBAT BELAJAR) - Putri, Rukiana Novianti; Nuraini, Pertiwi; Amsal, Bahrul (Universitas Muhammadiyah Makassar, 2023)
This research aims to determine the description of the creativity of slow learner students using a qualitative approach using purposive sampling techniques. The results of the research show that slow learner students are slow to understand the subject matter, have short attention span, slow reaction time, are lagging behind in academics, especially in reading, limited vocabulary, low retention and memory, low level of initiative, less stable emotional control and less capable. interact openly. The picture of creativity of slow learner students that emerged from the subjects is that they are able to express their ideas using attractive colors and shapes; able to tell stories with interesting and entertaining imagination; able to find ways to express themselves with rhythm and body movement through music. This shows that the picture of creativity of slow learner students in general can be a source of unexpected potential because each student has a unique way of showing their creativity. Despite the fact that students understand academic lessons more slowly than their classmates.